The Reality of Practicing the Knowledge Management at Al-Aqsa University in Gaza Strip from the prospective of the Administrative Staff - Abu AlSoud, Mohammed Hazem (Journal of Economic, Administrative and Legal Sciences, 2022)
This Study aims to identify the reality of practicing knowlge management at Palestinian universities, applying at alaqsa univesity in Gaza Strip, The study followed the descriptive analytical approach, and the questionnaire was used as a tool that was distributed to a random sample of (175) individual workers at Al-Aqsa University. Their averages are arranged as follows: Knowledge storage (3.83) Knowledge diagnosis (3.74) Knowledge sharing (3.70) Knowledge generation (3.57) Knowledge transfer (3.50) Knowledge distribution (3.43), all with a degree of practice (high), and the results showed that there were no differences according to the variables (age group, position occupational status, social status, specialization), while there were significant differences due to the gender variable, and in favor of (males). Depending on the results, the researcher recommended the necessity of establishing a knowledge management department at Al-Aqsa University.